Utilisation of marama bean [Tylosema esculentum (Burchell) A. Schreiber] flour in gluten-free bread making - De Kock, Henrietta Letitia (University of Pretoria, 2020)
Thesis (PhD (Food Science))--University of Pretoria, 2020.